Identification of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD)-inducible genes in human amniotic epithelial cells - Abe, Yumiko; Sinozaki, Hiromitsu; Takagi, Takeshi; Minegishi, Takashi; Kokame, Koichi; Kangawa, Kenji; Uesaka, Miki; Miyamoto, Kaoru (Reproductive biology and endocrinology, 2006)
Exposure to dioxins results in a broad range of pathophysiological disorders in human fetuses. In order to evaluate the effects of dioxins on the feto-placental tissues, we analyzed the gene expression in 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) treated primary cultures of human amniotic epithelial cells. Human amniotic epithelial cells were dispersed by trypsin from amniotic membranes and cultured in DME/Ham's F12 medium supplemented with 10% FBS. Two weeks after plating, cells were treated with 50 nM TCDD or DMSO (control), further incubated for 48 hrs, and the gene expression was analyzed by DNA microarray technology and quantitative real-time PCR. Thirty eight TCDD-inducible genes, including cytochromeP4501A1 and cytochromeP4501B1, were identified. One of the remarkable profiles of the gene expression was the prominent up-regulation of interferon-inducible genes. The genes involved in the interferon gene expression and interferon signaling pathways were also up-regulated. Furthermore, the expression of genes related to collagen synthesis or degradation was enhanced by TCDD. Using DNA microarray and quantitative real-time PCR analyses, we identified TCDD-inducible genes, including interferon-inducible genes and genes related to collagen synthesis or degradation, in human amniotic epithelial cells.